Effects of sulfate and chloride ions in acidic environments on the micro properties of granite - H Yu; C Zhang; H Chen; I Canbulat; S Saydam (The Australasian Institute of Mining and Metallurgy, 2024)
Natural rocks are frequently exposed to groundwater and complex geological conditions. Environments with water presence are more susceptible to chemical corrosion, which notably affects rock’s micro properties. Generally, the pH of acid mine drainage in hard rock mines can be low to 5, and the pH of quarrying waste deposits can be below 3. With the expanding scope of mining engineering in aquifers and salty areas, chemical corrosion can also caused by different types and concentrations of anions. The anions can significantly affect rock’s mechanical properties. Therefore, it is critical to emphasise the impact of anion and acid on the mechanical and micro characteristics of rock. This paper commences with an introduction to representative corrosive environments. Then the UCS tests are conducted on granite samples corroded by chloride ions and sulfate ions. Anion has negative effects on the strength of granite. The reason is that certain minerals can react and be dissolved by anions and hydrogen ions, such as Al2O3. Furthermore, the scanning electron microscope (SEM) shows that the roughness of the fracture surface increases with the anion concentration. The effect of acid is notably more pronounced than anion on the micro properties of granite. The initiated fissures and pores also increase with the concentration of SO42- and Cl- ions, which is the micro explanation for the impact of anion on rock strength and stability. Subsequently, the permeability of the granite specimens is tested. The reason that granite performs insensitivity to acid and anion is attributed to its low permeability and high content of inactive oxides, such as quartz. To summarise, anionic and acidic conditions can slightly deteriorate the mechanical and micro properties of granite. While SO42- demonstrates a higher level of corrosiveness on granite than Cl-.